G‐CSF rescues tumor growth and neo‐angiogenesis during liver metastasis under host angiopoietin‐2 deficiency. Issue 2 (3rd July 2012) - Im, Jae Hong; Tapmeier, Thomas; Balathasan, Lukxmi; Gal, Annamaria; Yameen, Sabira; Hill, Sally; Smart, Sean; Noterdaeme, Olivier; Kelly, Matthew; Brady, Michael; Fu, Weili; Kruse, Karoline; et al.
Abstract Suppression of neo‐angiogenesis is a clinically used anti‐tumor strategy with new targets such as angiopoietin‐2 (Ang2) being proposed. However, the functions of Ang2 in vascular remodeling, inflammation and tumor growth are not consistent. We examined effect of depletion of host Ang2 on liver colony formation using Ang2 deficient (Ang2−/−) mice. Surprisingly, the metastatic colonies formed in Ang2−/− mice were larger than those in the wild type. These colonies had greater vascular density with more pericyte coverage than the vessels in liver colonies in the wild type. Liver VEGF concentration in both genotypes was equivalent, and thus, the differences appeared VEGF independent. However, after colony formation, the serum concentration of granulocyte‐colony stimulating factor (G‐CSF) and CXCL1 in Ang2−/− mice was 12 and 6 times greater than after colony formation in wild type. Increase of these two cytokines was associated with two times greater numbers of neutrophils recruited to the liver. Two times more Tie2+/CD11b+/CD31− cells were present in the tumors in Ang2−/− than in the wild type livers. These results suggest that the depletion of host Ang2 induced compensatory VEGF‐independent angiogenic mechanisms and thus enhanced liver metastatic colony growth and colony vascularity. They further indicate organotypic differences in response to tumor metastasis. In contrast, Ang2 deficiency inhibited tumor growth during metastatic colony formation in the lung, consistent with the reports of decreased pulmonary seeding of tumor cells after pharmacological inhibition of Ang2. Further studies are thus required to assess the effects of pharmacological Ang2 blockade for cancer patients particularly in the liver.